POTENTIAL OF THE EXTRACT PIROLENHOSO: INTRODUCTORY CHARACTERIZATION OF PRACTICE - Sena, Marcelo Monteiro Fonseca de; Andrade, Azarias Machado de; Thode Filho, Sérgio; Santos, Felipe Rocha dos; Pereira, Letícia Ferreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The use of fossil primary energy sources has remained stable in the world with no prospect of change scenarios. Charcoal is one of these sources. The burning of wood for obtaining its coal emits into the atmosphere components that, once obtained through simple processes, enable significant commercial exploitation with great potential for expanding its use. The objective of this study was to characterize the early practices pirolenhoso extract by fractional distillation in Multidisciplinary Laboratory Waste Management IFRJ campus in Duque de Caxias. For the tests sampled a mass of 300g of crude extract and calculated your income after the distillation process. Was quantified mass tar (heavy phase), pirolenhoso fluid (lighter phase with all its composites) and loss in the process. Stoichiometric comparisons showed, though with little variability in the results, an average trend yield of approximately 64% of the samples with pirolenhoso liquid. 30% of distilled material was characterized as tar. Regarding losses in the process, the perceived average was 6% for the five samples.